The Effect Of Modernization Of The Tax Administration System And Taxpayer Awareness On Taxpayer Compliance - Irwansyah; Yudiana; Dali, Rahmat Mulyana (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2023)
This study aims to determine the effect of the Tax Administration Modernization System and Taxpayer Awareness on Taxpayer Compliance in Cimanggu Village 1. This research uses quantitative research methods, using primary data. The sample in the study used the Total Sampling Technique and obtained as many as 96 respondents. The regression analysis model used in this study is multiple linear regression analysis. Where the research results are in the form of presentation of statistical results that have been processed using SPSS software. Based on the analysis that has been carried out in this study, the results show that related to the influence of the Tax Administration System Modernization variable does not affect taxpayer compliance, Taxpayer Awareness has a positive and significant effect on Taxpayer Compliance variables and modernization of the tax administration system and taxpayer awareness has an effect on taxpayer compliance.